Serakahnomics dalam Perjanjian Kartel pada Kontrak Bisnis dan Risiko Kepailitan Sistemik - Asharin Sindy Safirah; Fonnyta Laurenzia Rosiga (Fakultas Hukum Universitas Islam Jember, 2026)
This study examines legal issues regarding the qualification of cartel agreements in the practice of serakahnomics, their mechanism for triggering systemic bankruptcy, and the legal certainty of bankruptcy requirements under Law No. 37 of 2004, to achieve justice. The objective is to analyze the relationship among cartels, serakahnomics, and systemic bankruptcy, and to formulate efforts to achieve justice in such disputes. Using a normative juridical method with a legal and conceptual approach, the results of the study show that cartel agreements are a clear manifestation of serakahnomics that can cause systemic bankruptcy. Therefore, it is necessary to reform Indonesian bankruptcy law, particularly in determining the requirements for filing for bankruptcy, in order to minimize systemic impacts while realizing fair law enforcement for national economic stability.